KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP PADA MATERI PELUANG DENGAN PENDEKATAN KONTEKSTUAL - Putri Tasya Monica; Muhammad Afrilianto; Euis Eti Rohaeti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This type of research is a classroom action research. This study aims to examine the improvement of mathematical problem solving ability of junior high school students on the opportunity material. This research was conducted on the students of class IX-C SMP Mahardhika Batujajar academic year 2017/2018 with the number of students 34 people. The instruments used are cycles I and II (after giving of action); and an observation sheet on teachers and students for the conditions of action implementation. The procedures of this study consist of: (1) Planning, (2) Implementation of action, (3) Observation and evaluation, and (4) Reflection. The results showed that students' mathematical problem solving ability in the subject matter could be improved through contextual approach.